Physiological Response of Reared Bali Cattle Based on Different Peat Land Characteristics - H. Hermawansyah; S. Salundik; Rudy Priyanto (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
This study aimed to investigate the effect of microclimate conditions within cattle houses at wet peatlands and dry peatlands on Bali cow's physiological responses. The study was carried out from November 2017 to February 2018 in Pulang Pisau Regency, Central Kalimantan Province. There were 58 heads of Bali cows used in this study, comprising 38 cattle at wet peatland in Jabiren Raya sub-district and 20 animals at a dry bog in Maliku sub-district. The observed parameters included microclimate conditions. It was air temperature, humidity, and temperature-humidity index, THI and wind speed, physiological responses (respiratory rate, pulse, and rectal temperature) and leucocyte (neutrophils, lymphocytes, and neutrophils/lymphocytes ratio). The results indicated that the morning microclimate at wet peatland showed significantly (p0.05) lower humidity, higher THI, and wind speed than that at dry land. The marked difference of microclimate between the two locations in the afternoon occurred only on wind speed. There were differences between dry and wet peatlands in Bali cow's physiological responses, including respiration rate in the morning, the pulse at noon, rectal temperature in the afternoon, and leucocyte. However, the local cattle' physiological responses kept in wet and dry peatland were still under normal conditions.